Formation of the radial electric field profile in the WEST tokamak. (16th December 2021) - Vermare, L.; Hennequin, P.; Honoré, C.; Peret, M.; Dif-Pradalier, G.; Garbet, X.; Gunn, J.; Bourdelle, C.; Clairet, F.; Morales, J.; Dumont, R.; Goniche, M.; et al.
Abstract: Sheared flows are known to reduce turbulent transport by decreasing the correlation length and/or intensity of turbulent structures. The transport barrier that takes place at the edge during improved regimes such as H mode, corresponds to the establishment of a large shear of the radial electric field. In this context, the radial shape of the radial electric field or more exactly of the perpendicular E × B velocity appears as a key element in accessing improved confinement regimes. In this paper, we present the radial profile of the perpendicular velocity measured using Doppler back-scattering system at the edge of the plasma, dominated by the E × B velocity, during the first campaigns of the WEST tokamak. It is found that the radial velocity profile is clearly more sheared in lower single null configuration (with the B × ∇ B magnetic drift pointing toward the active X -point) than in upper single null configuration for ohmic and low current plasmas ( B = 3.7 T and q 95 = 4.7), consistently with the expectation comparing respectively 'favourable' versus 'unfavourable' configuration. Interestingly, this tendency is sensitive to the plasma current and to the amount of additional heating power leading to plasma conditions in which the E × B velocity exhibits a deeper well in USN configuration. For example, while the velocity profile exhibits a clear and deep well just inside the separatrix concomitant with the formation of a density pedestal during L–H transitions observed in LSN configuration, deeper E r wells are observed in USN configuration during similar transitions with less pronounced density pedestal.